Structural phase coexistence and magnetocaloric effect in fast‐neutron‐irradiated Ce(Fe0.96Ru0.04)2 intermetallic compound. Issue 1 (16th September 2013) - Dube, V.; Mishra, P. K.; Sastry, P. U.; Prajapat, C. L.; Rajarajan, A. K.; Thakare, S. V.; Singh, M. R.; Ravikumar, G.
<x xml:space="preserve">Abstract</x> We have presented direct evidence of crystallographic structural phase coexistence in a fast‐neutron‐irradiated Ce(Fe0.96Ru0.04)2 intermetallic compound. The ferromagnetic (FM) cubic phase slowly transforms into antiferromagnetic (AFM) rhombohedral phase at low temperature. Though the FM to AFM transition is first order in nature, the coexistence continues well below the transition temperature. Using Maxwell's relation we have deduced the magnetic entropy change, ΔSM. Remnant FM domains nucleated around the quenched defects, created by fast‐neutron irradiation, is principally responsible for a diminution of ΔSM.